Determinants Of Application Of Balanced Nutrition Guidelines To Mothers Who Have Preschool Children (3-6 Years) During The Adaptation Of New Habits - Nengsih Nengsih; Eka Ratnasari; Nurhasanah Nurhasanah (JKM (Jurnal Kebidanan Malahayati), 2022)
Latar Belakang: Adaptasi Kebiasaan Baru merupakan wujud dari hadirnya Corona Virus Disease (Covid 19). Penyebaran Covid 19 sangat masif, tidak dapat dipungkiri bahwa Covid 19 merupakan salah satu jalan menuju kebiasaan baru dalam tatanan hidup yang lebih baik, terutama terkait dengan aspek kesehatan. Masyarakat akan lebih disiplin dalam menggunakan alat pelindung diri, secara mandiri mau dan mampu membuat prioritas dalam hal menjaga kebersihan diri dan lingkungan, termasuk kesadaran tentang pemenuhan pola pemenuhan gizi seimbang bagi anggota keluarga dalam kehidupan sehari-hari menjadi lebih baik.Tujuan: penelitian ini untuk melihat pola penerapan pedoman gizi seimbang bagi ibu yang memiliki anak (usia 3-6 tahun) selama adaptasi kebiasaan baru dan hubungannya dengan determinannya.Metode penelitian ini: merupakan penelitian analitik dengan pendekatan cross sectional. Penelitian ini akan melihat masing-masing determinan dan akan dilakukan uji Chi Squere untuk menjawab hipotesis penelitian, ada hubungan antara determinan dengan pola penerapan pedoman gizi seimbang pada ibu yang memiliki anak prasekolah (usia 3-6 tahun) . Penelitian ini dilakukan pada ibu yang memiliki anak pra sekolah (usia 3-6 tahun). Teknik pengambilan sampel yang digunakan adalah purposive sampling, dalam teknik ini ibu yang merupakan wali siswa pada TK di Kabupaten Cirebon. Teknik analisis data yang digunakan adalah analisis univariat dan bivariat dengan bantuan SPSS versi 23.Hasil penelitian menunjukkan hubungan umur dengan penerapan gizi seimbang diperoleh p-value = 0,000 (≤ 0,05). Hubungan antara pendidikan dan penerapan gizi seimbang diperoleh p-value = 0,002 (≤ 0,05). Hubungan pengetahuan dengan penerapan gizi seimbang dengan p-value = 0,000 (≤ 0,05).Kesimpulannya adalah terdapat hubungan antara determinan dengan penerapan gizi seimbang pada masa adaptasi kebiasaan baru, sehingga berdampak baik terhadap status kesehatan khususnya bagi kelompok rentan yaitu anak pra sekolah (3-6 bertahun-tahun).Saran: sosialisasi dan evaluasi berkala kepada orang tua yang memiliki anak prasekolah dan membina mitra penyelenggara pendidikan anak yang potensial. Kata kunci: Penerapan pedoman gizi seimbang, anak prasekolah, adaptasi kebiasaan baru ABSTRACT Background: Adaptation to New Habits is a manifestation of the presence of the Coronavirus Disease (Covid 19). The spreading of Covid 19 is very massive, it is undeniable that Covid 19 is one of the roads leading to new habits in a better order of life, especially related to the health aspect. The community will be more disciplined in using personal protective equipment, independently willing and able to make priorities in terms of maintaining personal and environmental hygiene, including awareness about fulfilling patterns of fulfilling balanced nutrition for family members in daily life for the better.The purpose: of this study was to see the pattern of application of balanced nutrition guidelines for mothers who have children (aged 3-6 years) during the adaptation of new habits and the relationship with its determinants. The methods of this research: is an analytic study with a cross sectional approach. This research will look at each determinant and the Chi Squere test will be carried out to answer the research hypothesis, there is a relationship between the determinants and the pattern of applying balanced nutrition guidelines for mothers who have preschool children (aged 3-6 years). This study was conducted on mothers who have pre-school children (aged 3-6 years). The sampling technique used was purposive sampling, in this technique, the mother who was the guardian of the student at the Kindergarten School in Cirebon Regency. The data analysis technique is univariate and bivariate analysis with SPSS version 23.The results showed the relationship between age and the application of balanced nutrition obtained p-value = 0.000 (≤ 0.05). The relationship between education and the application of balanced nutrition obtained p-value = 0.002 (≤ 0.05). The relationship between knowledge and the application of balanced nutrition with p-value = 0.000 (≤ 0.05). The conclusion is that there is a relationship between the determinants and the application of balanced nutrition during the adaptation period for new habits, so that it has a good impact on health status, especially for vulnerable groups, namely pre-school children (3-6 years). Suggestion: periodic socialization and evaluation to parents who have preschool children and building the partners of potentially childhood education prividers. Keywords: Application of balanced nutrition guidelines, preschool children, the adaptation of new habit